Development of the embryonic neuromuscular synapse of Drosophila melanogaster - Broadie, KS (J Neurosci, 1993)
We have examined the embryonic development of an identified neuromuscular junction (NMJ) of Drosophila melanogaster using whole- cell patch-clamp and a variety of physiological and morphological techniques. Synaptic current at the embryonic NMJ is carried through a large-conductance (200 pS) L-glutamate receptor. Early synaptic communication is characterized by frequent, brief (< 10 msec) currents carried through few (1–10) receptors and relatively rare, prolonged currents (up to seconds) of similar amplitude. The brief currents have a time course similar to the mature larval excitatory junction currents (EJCs), but the prolonged currents are restricted to early stages of synaptogenesis. The amplitude of EJCs rapidly increases, and the frequency of the prolonged currents decreases, after the initial stages of synaptogenesis. Early prolonged (seconds), nonspiking synaptic potentials are replaced with rapid (> 0.10 sec), spiking synaptic potentials later in development. The early synapse appears tenuous, easily fatiguable, and with inconsistent communication properties. Synaptogenesis can be divided into a sequence of progressive stages. (1) Motor axon filopodia begin neurotransmitter expression and concurrent exploration of the myotube surface. (2) Myotubes uncouple to form single-cell units soon after motor axon contact. (3) A small number of transmitter receptors are homogeneously displayed on the myotube surface immediately following myotube uncoupling. (4) Endogenous transmitter release from pioneering growth cones is detected; nerve stimulation elicits postsynaptic EJC response. (5) Motor axon filopodia and transmitter receptors are localized to the mature synaptic zone; filopodial localization is complete in advance of receptor localization. (6) A functional neuromuscular synapse is formed; endogenous muscular activity begins; nerve stimulation leads to muscle contraction. (7) Morphological presynaptic specializations develop; synapse develops mature morphology. (8) A second motor axon synapses on the myotube at the pre-established synaptic zone. (9) Vigorous neuromuscular activity, characteristic of larval locomotory movements, begins. (10) A second stage of receptor expression begins and continues through the end of embryogenesis. In general, Drosophila neuromuscular synaptogenesis appears similar to neuromuscular synaptogenesis in known vertebrate preparations. We suggest that this system provides a model for synaptogenesis in which investigation can be readily extended to a genetic and molecular level.